Exploratory analysis of a Novel RACK1 mutation and its potential role in epileptic seizures via Microglia activation - Sai Zhang; Zhaofei Dong; Jing Guo; Ze Li; Hong Wu; Linming Zhang; Fuli Min; Tao Zeng (Journal of Neuroinflammation)
Abstract Seizures is a prevalent neurological disorder with a largely elusive pathogenesis. In this study, we identified the key gene RACK1 and its novel mutation RACK1-p.L206P as being associated with seizures through single-cell transcriptome sequencing (scRNA-seq) and whole exome sequencing (WES) techniques. Our findings reveal that the RACK1-p.L206P mutation significantly enhances proliferation, migration, phagocytic ability, and inflammatory activation in human microglia, which in turn affects neuronal excitability and synaptic function, culminating in typical seizure symptoms in the seizures. These effects were further validated in a mouse model using CRISPR/Cas9 gene editing technology. Mutant microglia exhibited increased activation and induced apoptosis in hippocampal neurons, leading to higher action potential frequency and excitatory synaptic marker expression. In vivo experiments demonstrated that RACK1-p.L206P mutant mice displayed classic seizure symptoms, with increased neuronal excitability and a tendency for action potential bursts during initial depolarization, along with more frequent spike discharges. Additionally, excitatory synapse density and size in the hippocampal CA1 region of mutant mice were significantly elevated, accompanied by increased expression of VGLUT1 and PSD95 within microglia. This study offers novel insights into the molecular mechanisms underlying seizures in the seizures and presents valuable clues for the development of future therapeutic strategies.